Como as perceções de climas autentizóticos explicam os comportamentos inovadores e o desempenho individual: o caso de uma multinacional - Matos, Joana; Ribeiro, Neuza (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
This study investigates how the perception of authentizotic climate (camaraderie spirit; leader trust and credibility; the open and frank communication with the leader; learning opportunities and personal development; equity / justice; work-family conciliation) explain the innovative behavior and individual performance. The data was analyzed from a questionnaire answered by 128 employees of a multinational. The results suggest that (1) the employees perception of camaraderie spirit explain their innovative behavior, (2) the fairness / justice perception and open and frank communication with the leader explains the individual performance, (3) the innovative behavior influences individual performance. In spite of the study limitations, empirical evidence suggests that organizations should promote the authentizotic climate, particularly the camaraderie spirit, the open and frank communication with the leaders and the equity/justice, if they want employees to adopt more innovative behavior and improve their individual performances.